1989
DOI: 10.1002/ajp.1350180103
|View full text |Cite
|
Sign up to set email alerts
|

Hominoid dental variability and species number at the late Miocene site of Lufeng, China

Abstract: The large hominoid sample from the late Miocene site of Lufeng, China, has been variously claimed to contain either one or two species, but very few metric data in support of either position have been published. We calculate coefficients of variation for the dental remains both for the two presumed species and for the pooled sample as a whole using the summary statistics published by Wu & Oxnard (Wu & Oxnard: American Journal of Primatology 5:303–344, 1983a, Nature 306:258–260, 1983b). These are compared to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…It has been suggested that this reflects the presence of two species at the site (Wu and Oxnard, 1983a,b;Martin, 1991;Cope andLacy, 1992, 1994;Plavcan, 1993b). However, others maintain that the sample is composed of a single, extremely dimorphic species (Wu, 1987;Kelley and Etler, 1989;Kelley and Xu, 1991;Wood and Xu, 1991;Kelley, 1993). Most recently, Kelley and Plavcan (1998) demonstrated that the pattern of metric variation in the sample is most consistent with the presence of a single species more dimorphic than any living hominoid.…”
Section: Dimorphism In the Primate Fossil Recordmentioning
confidence: 99%
“…It has been suggested that this reflects the presence of two species at the site (Wu and Oxnard, 1983a,b;Martin, 1991;Cope andLacy, 1992, 1994;Plavcan, 1993b). However, others maintain that the sample is composed of a single, extremely dimorphic species (Wu, 1987;Kelley and Etler, 1989;Kelley and Xu, 1991;Wood and Xu, 1991;Kelley, 1993). Most recently, Kelley and Plavcan (1998) demonstrated that the pattern of metric variation in the sample is most consistent with the presence of a single species more dimorphic than any living hominoid.…”
Section: Dimorphism In the Primate Fossil Recordmentioning
confidence: 99%
“…Assuming that YV0999 is representative of cranial morphology in other Lufengpithecus species (SI Text), we consider it most probable that Lufengpithecus represents a stem hominid lineage that also expresses a small suite of uniquely derived features (4,9,23). It is also possible given the general resemblance to Pan, exclusive of the derived features of extant African apes noted in Table 1, that Lufengpithecus represents a stem member of the African ape and human clade (20) (discussed further below).…”
Section: Discussionmentioning
confidence: 99%
“…Restoration has been attempted for one of these (8), but some of the morphology remains ambiguous or is clearly still distorted. The condition of these crania has allowed for different interpretations of their morphology and, consequently, different opinions regarding the phylogenetic position of Lufengpithecus (4,(8)(9)(10)(11). Nevertheless, most recent analyses propose a relationship to the Pongo clade, as either its nearest relative or as a stem member of the clade (12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Methodologically, there is a choice of several different measures of variability: the coefficient of variation (CV), the maximum/minimum index (max/min), range based proportions of the mean (R%), and the sexual dimorphism index (SDI). Although the criticisms of each statistic are numerous and the literature voluminous, it appears that the CV is the measure of choice for most palaeontologists (Cope, 1989(Cope, , 1993Cope & Lacy, 1992;Kay, 1982aKay, ,1982bKay & Simons, 1983;Kelley, 1986Kelley, , 1993Kelley & Etler, 1989;Martin, 1983;Martin & Andrews, 1984Pan et al, 1989;Plavcan, 1989Plavcan, , 1990Plavcan, , 1993Tattersall, 1986;Teaford et al, 1993;Wood & Xu, 1991). However, all statistics share a basic set of theoretical assumptions:…”
Section: Primate Palaeontological Problem Orientationmentioning
confidence: 95%